Event Sponsorship Service Quality at PT Sinar Sosro East Java Region: A Gap Analysis - Phima Ruthia Dwikesumasari; Rachmatullah Dwi Nugraha (Universitas Airlangga, 2019)
Traditional marketing communication media begin to be abandoned by customers; therefore, companies need to find other more effective alternatives to communicate with customers. Companies try to convince that customers not only use the the products they bought but also get unforgetable experience. Thus, companies often hold experiential marketing in the form of event as one of the alternatives. One of the efficient ways to conduct event marketing activities is by establishing an event sponsorship and building collaboration with event organizers. One of many companies which prioritizes its event sponsorship is PT Sinar Sosro East Java Region Representative Office. To be able to maintain the continuity of this program, PT Sinar Sosro East Java Region Representative Office needs to pay attention to the quality of event sponsorships services provided by company’s Marketing support Division. The purpose of this study is to analyze customer evaluation that is the event organizers, for the quality of company’s sponsorhip event services. In line with this purpose, this study used a 5-scale Likert measurement from the 5 dimension SERVQUAL measurement items with gap analysis techniques. Samples were taken using a proportional stratified random sampling method, resulted a minimum sample size of 97 respondents. Questionnaires were sent to 115 respondents but only 101 which could be analyzed further. Results showed that PT Sinar Sosro East Java Region Representative Office sponsorship event services was rated good since most of the results from gap analysis of each items of questionnaire statements showed a positive scores. Although some negative scores appeared, it did not dominate the overal result. The negative scores appeared on several items on tangibles, reliability and responsiveness dimensions. Overall positive scores were existed on assurance dimension, which consisted of the most statement items on this questionnaire, and empathy dimension. This indicated that the level of service received by customers had exceeded the service level expected by them.